Contrasting Effects of Extreme Drought and Snowmelt Patterns on Mountain Plants along an Elevation Gradient - Rosbakh, Sergey; Leingärtner, Annette; Hoiss, Bernhard; Krauss, Jochen; Steffan-Dewenter, Ingolf; Poschlod, Peter (Frontiers in Plant Science, 2017)
Despite the evidence that increased frequency and magnitude of extreme climate events (ECE) considerably affect plant performance, there is still a lack of knowledge about how these events affect mountain plant biodiversity and mountain ecosystem functioning. Here, we assessed the short-term (one vegetation period) effects of simulated ECEs (extreme drought (DR), advanced and delayed snowmelt (AD and DE, respectively) on the performance of 42 plant species occurring in the Bavarian Alps (Germany) along an elevational gradient of 600 to 2000 m a.s.l. in terms of vegetative growth and reproduction performance. We demonstrate that plant vegetative and generative traits respond differently to the simulated ECEs, but the nature and magnitude treatment effects strongly depend on study site location along the elevational gradient, species’ altitudinal origin and plant functional type of the target species. For example, the negative effect of DR treatment on growth (e.g. lower growth rates and lower leaf nitrogen content) and reproduction (e.g. lower seed mass) was much stronger in upland sites, as compared to lowlands. Species’ response to the treatments also differed according to their altitudinal origin. Specifically, upland species responded negatively to extreme drought (e.g. lower growth rates and lower leaf carbon concentrations, smaller seed set), whereas performance of lowland species remained unaffected (e.g. stable seed set and seed size) or even positively responded (e.g. higher growth rates) to that treatment. Furthermore, we were able to detect some consistent differences in responses to the ECEs among three plant functional types (forbs, graminoids, and legumes). For instance, vegetative growth and sexual reproduction of highly adaptable opportunistic graminoids positively responded to nearly all ECEs, likely on the costs of other, more conservative, forbs and legumes. Our results suggest that ECEs can significantly modify the performance of specific plant groups and therefore lead to changes in plant community structure and composition under ongoing climate change. Our study therefore underlines the need for more experimental studies on the effects of extreme climate events to understand the potential consequences of climate change for the alpine ecosystem.